Study of Phytochemistry and Potential of Endophyte Fungi Extract in Avicennia marina Roots as Antioxidants Inhibiting Early Aging - Muhammad Andhika Pratama; Mochammad Agung Seno Pambudi; Eri Bachtiar; Mochamad Rudyansyah Ismail; Yeni Mulyani; Sulastri Arsad; Fiddy Semba Prasetiya (Journal of Aquaculture and Fish Health, 2022)
The mangrove plants has long been utilized as traditional medicinal ingredients for treatments of various diseases in favour of bioactive components from its secondary metabolites. Secondary metabolites from mangroves could act as an antioxidant to prevent oxidative stress. Mangrove may contain endophyte fungi in its tissues that are capable of producing secondary metabolites. In theory, endophyte fungi isolated from a plant can produce secondary metabolites similar to those of the original plants or even in relatively high numbers. In this research, mangrove species Avicennia marina was sampled from Blanakan, Subang District, West Java. Endophyte fungi were isolated from the mangrove roots that had been obtained. The experimental method was used to test antioxidant activitiy using DPPH (1,1-diphenyl-2-picrylhidrazyl) method and phytochemical content, with three replicates for each tests. Fungal isolates were coded according to the distance of the roots from the main mangrove tree, namely STAD and STAJ that represents “close” and “far” roots. Our results showed that the enviromental parameters, namely salinity, dissolved oxygen, and temperature meet the quality standards and mangrove life in the tropics. The A. marina type of substrate muddy soil and has a pH value, which did not meet the quality standards for mangrove waters. As for antioxidant activity, both extracts could reduce DPPH free radicals. Further determination of the IC50 value of the two extracts showed that the endophytic fungi STAD and STAJ had IC50 values of 97.8 ppm (classified as strong) and 822.56 ppm (classified as very weak) in the DPPH radical immersion method. Phytochemical test revealed that the two extracts of fungal isolates contain bioactive compounds, where flavonoids and alkaloids were identified in isolate STAD, whereas STAJ was positive for tannins and alkaloids content.